Learning English and Chinese as foreign languages : sociocultural and comparative perspectives - Lin, Wen-Chuan (New Perspectives on Language and Education, 2019)
Learning English and Chinese is becoming increasingly important to the prospects of young people. This book compares English as a Foreign Language teaching in Taiwan with Chinese as a Foreign Language education in England in order to highlight how classroom activities are embedded within multiple settings, including ethnic or other social group cultures, family and community resources and school visions or goals. The book illustrates how in Taiwan different ethnic groups recognise, access and value English language learning to varying extents. Its findings illuminate why some ethnic groups are highly motivated to learn English and are able to gain privileged economic positions in the job market. In England, access to Chinese is marked by social class, and the book argues that this could augment an 'educational apartheid' that already exists in language teaching in secondary schools, thereby exacerbating existing inequality.